190k views
4 votes
1+cos2a+sin2a/1-cos2a+sin2a=cota

User Ckuri
by
5.6k points

1 Answer

2 votes

Answer:

Proved

Explanation:

Required

Show that:


(1+cos2a+sin2a)/(1-cos2a+sin2a)=cota


cos2a = cos(a + a) = cos^2a - sin^2a

So, we have:


(1+cos^2a - sin^2a+sin2a)/(1-(cos^2a - sin^2a)+sin2a)=cota


(1+cos^2a - sin^2a+sin2a)/(1-cos^2a + sin^2a+sin2a)=cota


1- cos^2a = sin^2a

So, we have:


(1+cos^2a - sin^2a+sin2a)/( sin^2a+ sin^2a+sin2a)=cota


(1+cos^2a - sin^2a+sin2a)/(2sin^2a+sin2a)=cota

Rearrange the numerator


(1 - sin^2a+cos^2a+sin2a)/(2sin^2a+sin2a)=cota


1- sin^2a= cos^2a

So, we have


(cos^2a+cos^2a+sin2a)/(2sin^2a+sin2a)=cota


(2cos^2a+sin2a)/(2sin^2a+sin2a)=cota


sin2a = 2sina\ cosa

So, we have:


(2cos^2a+2sinacosa)/(2sin^2a+2sinacosa)=cota

Factorize:


(cosa(2cosa+2sina))/(sina(2sina+2cosa))=cota

Rewrite as:


(cosa(2cosa+2sina))/(sina(2cosa+2sina))=cota


(cosa)/(sina) = cota


cota = cota

User Wray Bowling
by
5.9k points